The rights of juries defended : together with authorities of law in support of those rights and the objections to Mr. Fox's libel bill refuted / By Charles Earl Stanhope ... - Stanhope, Charles Stanhope, Earl, 1753-1816. (Tufts University. Tisch Library., 2016)
1 online resource ([4], 164 pages).; With a half-title.; Signatures: [A]² B-X⁴ Y².; Electronic reproduction. Medford, MA : Tisch Library, Tufts University, 2015. Scanned by the Boston Library Consortium/Open Content Alliance as part of the BLC OCA Digitization Project from a copy at the Tisch Library, Tufts University.; Indexed in: English Short Title Catalog,ESTCT140652